2020
DOI: 10.1021/acs.jchemed.9b01157
|View full text |Cite
|
Sign up to set email alerts
|

Transition to eBook Provision: A Commentary on the Preferences and Adoption of eBooks by Chemistry Undergraduates

Abstract: When the word textbook is used, the common image in our minds is that of a physical book, but textbook provision has been impacted by the revolution in digital technology. eBooks are now commonplace in higher education with many university libraries moving to an “e-first” policy. The attitudes of chemistry undergraduates to printed and digital texts were explored using survey data and library analytics. Results suggest that chemistry students have not fully embraced the use of ebooks in their reading, and depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Upon more in-depth screening of these articles, we excluded 4 that did not fit our inclusion criteria. The final sample included 79 studies. While we intend this review to be comprehensive, we acknowledge the possibility of unintentional omissions. Of note is that none of the articles in this review are written by the authors of this manuscript.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon more in-depth screening of these articles, we excluded 4 that did not fit our inclusion criteria. The final sample included 79 studies. While we intend this review to be comprehensive, we acknowledge the possibility of unintentional omissions. Of note is that none of the articles in this review are written by the authors of this manuscript.…”
Section: Methodsmentioning
confidence: 99%
“…29 These studies used a variety of methods: surveys, 29,38,39,56,64,74,75 surveys and interviews, 16,21 and some tested student comprehension of the textbook content with assessments. 12,40,61,67,70,72 A subset of these studies examined student use of ebooks 38,39 or open educational resources (OERs). 40,70,75 Three of these studies asked students to complete surveys to compare ebooks/OERs and traditional textbooks 38,39,75 and two examined the difference in student assessment scores when using ebooks/OERs and traditional textbooks.…”
Section: Characterization Of the Various Aspects Of Chemistry Textbooksmentioning
confidence: 99%
See 1 more Smart Citation
“…Linda and Michele described the act of finding a relevant section in the e-text taking more steps compared with printed text, and conveyed a preference for printed text for such activities. A recent study on chemistry students' usage of e-text and printed text reported that students liked the e-text for its low cost and ease of searching for a specific term or phrase (via a search feature); however, they reported the printed text as easier to read and annotate, and having fewer distractions [14]. It is not clear how the etext user interface and features used in our context compares with that of this recent study, and course context (e.g., chemistry or physics) may play an important role in how students perceive and engage with any form of course textbook.…”
Section: Barriersmentioning
confidence: 99%
“…Adoption of OER textbooks and comparisons to print textbooks have previously been studied across disciplines [10][11][12][13][14] and within the context of introductory physics courses [15]. One may find a recent literature review of students' engagement with e-texts versus paper texts particular helpful for more information on this topic [16].…”
Section: Introductionmentioning
confidence: 99%